Penerapan Problem Based Learning Untuk Meningkatkan Motivasi Belajar Peserta Didik Pada Pembelajaran Tematik Tema 8 Daerah Tempat Tinggalku Di Kelas IV SDN 19 Mataram 2022/2023 - Dina Apriani; Muhammad Tahir; Irma Suryani Rizki (Journal of Science Instruction and Technology, 2023)
This study was conducted to enhance students' motivation in topic-based learning on Topic 8 "The Area Where I Live, Mataram" using Problem Based Learning (PBL) model in Class IV in SDN 19 Mataram. This type of research is called Research in the Classroom (PTK). The subjects of the study were 22 students of class IV SDN 19 Mataram, including 4 female and 18 male students. The PTK design uses the Kemmis and Taggart model, which includes planning, action, observation and reflection. Data collection methods use questionnaires to observe and motivate learning. Qualitative descriptive statistics were used to analyze the data. The results of the study show that there is an increase in student motivation, this can be judged by the increase in motivation that occurs in each cycle, namely in the pre-cycle the percentage of student motivation is 56%, in the first cycle the percentage of student motivation is 71%, and in the second cycle the percentage motivation - 81%. Thus, it can be concluded that the use of problem-based learning (PBL) teaching model can enhance the motivation of students of class IV SDN 19 Mataram.